ANALISIS LOYALITAS KONSUMEN PRODUK BERLABEL HALAL - Nurul Izzah Lubis (AL-QARDH, 2019)
This article aims to determine how much is the influence the product quality, brand image and halal label to consumer loyalty product of PT. Unilever Indonesia. The research method used is quantitative approach with multiple linear regression analysis. The research used primer and secondary data from consumer product of PT. Unilever Indonesia in Desa Hutaraja. The result of the research showed that there was the positif influence of product quality and brand image variable to the consumer loyalty product of PT. Unilever Indonesia in Desa Hutaraja. The result of the research also showed that there was not influence of  halal label variable to the consumer loyalty product of PT. Unilever Indonesia in Desa Hutaraja.